1999
DOI: 10.1108/eb021097
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale Engineering project process and user requirements

Abstract: This paper presents results from an analysis of Large Scale Engineering (LSE) project process conducted within the ESPRIT 20876 project ‘eLSEwise’. The paper describes the LSE project processes, interfaces with business processes, the effects of the changing market place, and current process barriers. In searching how these barriers can be reduced or eliminated, the LSE industry information requirements and Information and Communications Technologies (ICT) requirements were explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Some of the findings from the various workshops and the results of the supplementary studies are reported in other publications ( Hassan et al 1999 ; Male and Mitrovic 1999; Melson and Kronstam 1999; Mitrovic et al . 1999 ; Zantke and Mangels 1999).…”
Section: Approach Adoptedmentioning
confidence: 65%
“…Some of the findings from the various workshops and the results of the supplementary studies are reported in other publications ( Hassan et al 1999 ; Male and Mitrovic 1999; Melson and Kronstam 1999; Mitrovic et al . 1999 ; Zantke and Mangels 1999).…”
Section: Approach Adoptedmentioning
confidence: 65%
“…This is important to any industry and company that wishes to serve global market. LSE projects add an additional dimension to it because they bring global resources to be transformed at a local scene and the output of the process has to serve socio‐economic needs ( Mitrovic et al 1999 ). Good local knowledge provides a contractor with an understanding of the socio‐economic environment within which it has to operate.…”
Section: Summary and Conclusion: The Key Sources Of Competitive Advamentioning
confidence: 99%